2020
DOI: 10.1126/sciadv.aay8189
|View full text |Cite
|
Sign up to set email alerts
|

On the glacial-interglacial variability of the Asian monsoon in speleothem δ 18 O records

Abstract: While Asian monsoon (AM) changes have been clearly captured in Chinese speleothem oxygen isotope (δ18O) records, the lack of glacial-interglacial variability in the records remains puzzling. Here, we report speleothem δ18O records from three locations along the trajectory of the Indian summer monsoon (ISM), a major branch of the AM, and characterize AM rainfall over the past 180,000 years. We have found that the records close to the monsoon moisture source show large glacial-interglacial variability, which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 90 publications
(121 reference statements)
3
44
0
Order By: Relevance
“…The red star is the location of Lugu Lake (this study). The circles with letters or numbers inside are the locations of speleothem (blue) or marine (dark blue) records in the Indian summer monsoon region and speleothem (green) records in the East Asian summer monsoon region, including (b) Southeast Yunan (SEY) caves (G. Liu, Li, et al, 2020), (c) Xiaobailong Cave (Cai et al, 2015), (d) Coastal Bay of Bengal (CBoB) caves (G. Liu, Li, et al, 2020), (e) Mawmluh Cave (Dutt et al, 2015), (f) Bittoo Cave (Kathayat et al, 2016), (g) core SO188-342 KL in the northern Bay of Bengal (Contreras-Rosales et al, 2014), (h) core RC12-344 in the Andaman Sea (Rashid et al, 2007), (i) core SK218/1 in the western Bay of Bengal (Govil & Naidu, 2011), (1) Dongge Cave (Cheng et al, 2016), (2) Sanbao Cave (Cheng et al, 2016), (3) Hulu Cave (Cheng et al, 2016). clockwise east-to-west wind direction in the western Pacific Ocean (Figure 1a).…”
Section: Study Region and Sitementioning
confidence: 99%
See 2 more Smart Citations
“…The red star is the location of Lugu Lake (this study). The circles with letters or numbers inside are the locations of speleothem (blue) or marine (dark blue) records in the Indian summer monsoon region and speleothem (green) records in the East Asian summer monsoon region, including (b) Southeast Yunan (SEY) caves (G. Liu, Li, et al, 2020), (c) Xiaobailong Cave (Cai et al, 2015), (d) Coastal Bay of Bengal (CBoB) caves (G. Liu, Li, et al, 2020), (e) Mawmluh Cave (Dutt et al, 2015), (f) Bittoo Cave (Kathayat et al, 2016), (g) core SO188-342 KL in the northern Bay of Bengal (Contreras-Rosales et al, 2014), (h) core RC12-344 in the Andaman Sea (Rashid et al, 2007), (i) core SK218/1 in the western Bay of Bengal (Govil & Naidu, 2011), (1) Dongge Cave (Cheng et al, 2016), (2) Sanbao Cave (Cheng et al, 2016), (3) Hulu Cave (Cheng et al, 2016). clockwise east-to-west wind direction in the western Pacific Ocean (Figure 1a).…”
Section: Study Region and Sitementioning
confidence: 99%
“…In the ISM region, some studies use the "amount effect" to interpret reconstructed changes in δ 18 Oc records based on modern observations, with lower δ 18 Oc values indicating more local or regional rainfall amount, and vice versa (Dansgaard, 1964;Cai et al, 2012;G. Liu, Li, et al, 2020).…”
Section: Origin Of Long-chain N-alkanes In Lugu Lake and Interpretation Of Reconstructed Rainfall Isotopesmentioning
confidence: 99%
See 1 more Smart Citation
“…But this hypothesis also needs to be tested by more sophisticated simulations. (3) Recently, Liu et al (2020a) found that speleothem δ 18 O records close to the ASM moisture source have a larger range of glacial-interglacial variability, which then decreases landward. It was then proposed that the moisture oxygen isotope fractionation during the transport from the ocean to the interior of the continent in the glacial period was significantly larger than in the interglacial period due to the larger temperature gradient and the weaker plant transpiration effect.…”
mentioning
confidence: 99%
“…Our result is contrary to the conclusions of several previous studies in stalagmite δ 18 O records and isotope-embedded climate simulations in EAM region, which emphasize the role of upstream processes in the tropical Indian Ocean in depleting precipitation δ 18 O in the EAM region [16][17][60][61][62] . However, the significance of these processes in Indian Ocean on the EAM stalagmite δ 18 O is not supported by the notable difference of stalagmite δ 18 O records between the EAM and ISM regions in terms of phase, variation amplitude and pattern on the glacial-interglacial as well as shorter than millennial time scales 13,[63][64][65][66][67][68] . Therefore, our results could provide a new perspective for interpreting stalagmite δ 18 O records in EAM region.…”
Section: Discussionmentioning
confidence: 99%